Fabrication Techniques for Graphene Oxide-Based Molecular Separation Membranes: Towards Industrial Application - Ohchan Kwon; Yunkyu Choi; Eunji Choi; Minsu Kim; Yun Chul Woo; Dae Woo Kim (Nanomaterials, 2021)
Graphene oxide (GO) has been a prized material for fabricating separation membranes due to its immense potential and unique chemistry. Despite the academic focus on GO, the adoption of GO membranes in industry remains elusive. One of the challenges at hand for commercializing GO membranes lies with large-scale production techniques. Fortunately, emerging studies have acknowledged this issue, where many have aimed to deliver insights into scalable approaches showing potential to be employed in the commercial domain. The current review highlights eight physical methods for GO membrane fabrication. Based on batch-unit or continuous fabrication, we have further classified the techniques into five small-scale (vacuum filtration, pressure-assisted filtration, spin coating, dip coating, drop-casting) and three large-scale (spray coating, bar/doctor blade coating, slot die coating) approaches. The continuous nature of the large-scale approach implies that the GO membranes prepared by this method are less restricted by the equipment’s dimensions but rather the availability of the material, whereas membranes yielded by small-scale methods are predominately limited by the size of the fabrication device. The current review aims to serve as an initial reference to provide a technical overview of preparing GO membranes. We further aim to shift the focus of the audience towards scalable processes and their prospect, which will facilitate the commercialization of GO membranes.